Numerical study on heat transfer and pressure drop characteristics of R410A condensation in horizontal circular mini/micro‐tubes. (12th July 2016) - Zhang, Jingzhi; Li, Wei
Abstract: Heat transfer and pressure drop characteristics of condensation for R410A inside horizontal circular tubes with inner diameters ranging from 0.25–4 mm were investigated numerically. The effects of mass flux, vapour quality, tube diameters, and gravity on heat transfer and pressure drop characteristics were discussed. Liquid‐vapour interfaces and stream‐traces were also presented to give a better understanding of these effects on the condensing flow. Numerical heat transfer coefficients and pressure gradients fitted well with the empirical correlations. The results indicate that local heat transfer coefficients and pressure drop increase with increasing mass flux, vapour quality, and with decreasing tube diameters. A thin liquid film is formed at the upper part of the tube in mini‐channels, while a symmetrical annular flow is observed in microchannels. A vortex with its core lying at the bottom of the tube is formed in the tubes with an inner diameter of 4 mm, while the stream‐traces start from the z ‐axis and point to the liquid‐vapour interface when d h is 0.25 mm. The gravity effect on heat transfer is important in larger tubes at lower vapour quality, where stratified flow may occur.